MEDIA DAN POLITIK : STRATEGI KAMPANYE PARTAI PERINDO DAN PSI DALAM MEMPENGARUHI SUARA PEMILIH DI KOTA SEMARANG - Sultoni, Ken Bimo; Harsasto, Priyatno (Journal of Politic and Government Studies, 2020)
Today's media is no longer just a means of conveying messages from communicants to one-way communicators that are rigid and passive, but has become a highly favored tool in winning a political contestation to influence voters' votes. The relationship between the media and the political process is essentially dialectical, in which actions and reactions occur. The media reports and analyzes political activity, on the contrary it also becomes part of the political process, because with the media political actors can find out the needs of the audience and deliver their political message to the audience.In the last General Election, several new parties emerged, including using the power of the media as part of their campaign strategy to attract voters, namely the Indonesian Unity Party or Perindo and the Indonesian Solidarity Party or PSI. These two parties together carry the power of the media but on the other hand get different results from each other. An example is the superiority of PSI compared to Perindo in obtaining the acquisition of two seats in the District Parliament This study uses a qualitative method with comparative studies. This method aims to explore and understand a central phenomenon and compare a phenomenon to get a fundamental answer about causation. Data collection techniques used were interviews, document review and literature. Informants in this study were Chairman of the Semarang City PSI Regional Board, Chairman of the Semarang City Perindo Regional Board, Political Observer and several Semarang City Communities.Â The difference in results obtained from the two parties that are both actively using the media is what influenced the author to try to raise this case as part of the main topic in this authorship study. The author tries to find out what caused the difference can occur and why it can occur. This authorship also tries to prove a case study that shows that the media, especially social media, does not necessarily increase the votes obtained during direct elections.Keywords: Media and Politics, Digital Political Campaign, General Elections.Â